Sistem Pakar Penanganan Kasus Sengketa Tanah Menggunakan Metode Backward Chaining - Sapri sapri; Khairil Khairil (Jurnal Teknik, 2019)
Land dispute is a conflict between two or more parties that have different interests in one or several objects of land rights that can result in legal consequences for both. Problems to explain government regulations and legislation relating to land dispute cases in a simple way that is, explained the rules that correspond to the problems that occur. This makes it difficult for a lawyer to deal with many clients and different cases. The purpose of this study is to design the Expert System for Handling Land Dispute Cases using the Backward Chaining Method. The study was conducted to analyze the existing needs, collect data, design, implement the results of the design into the application that is used, after that will be tested and maintained the system. The results of the study show that the existence of this expert system, it provides very meaningful benefits for the client, namely facilitating the client to carry out consultations regarding the handling of land dispute cases.